Effects of strain path and girth weld heterogeneity on strain limits of X70 pipeline. (August 2022) - Cao, Jun; Ma, Weifeng; Hui, Wenying; Wang, Ke; Cai, Ke; Li, Xiaolong; Cong, Shen; Ren, Junjie; Nie, Hailiang; Dang, Wei
Abstract: Geological disasters frequently cause pipeline failure. Therefore, the strain limits of pipelines under various strain paths should be carefully considered to provide the critical strain, particularly for girth welds. The iterative method was used to determine local accurate constitutive relations for the three typical zones of X70 girth weld: base material (BM), heat affected zone (HAZ), and welding metal (WM). By combing accurate constitutive equations of local deformation with a modified elliptical fracture criterion. The prediction strain limits were then verified using a hybrid experimental-numerical method with four geometries (uniaxial tension, tension with notch, flat-groove tension, and pure shear specimens) and three zones (BM, HAZ, and WM). The microstructure and fractography of BM, HAZ, and WM zones were analyzed to investigate the difference in strain limits under different strain paths. The results demonstrate that in tension stress states, the strain limits of WM for under-matched girth welds are the weakest, while the tension-compression asymmetry for WM is the greatest. As a result, when a pipeline is under tension, the girth weld is prioritized for protection. On the other side, the pipeline itself focuses on protection in compression to avoid buckling. Furthermore, the ferrite content is mostly responsible for the contribution of strain limits for these zones. The lower strain limit of WM in the tensile state is attributable to the inclusions in the welding process. Graphical abstract: Image 1 Highlights: The strain limits under different strain paths for BM, HAZ, and WM were predicted. The accurate local constitutive equation was coupled with the fracture criterion. The tension-compression asymmetry was analyzed in the girth weld and BM. A hybrid experimental-numerical method was used to verify the fracture loci.